Kinetic properties of gill (Na+, K+)-ATPase in the Pacific whiteleg shrimp Penaeus vannamei (Decapoda, Penaeidae) - Moraes, Cintya M.; Fabri, Leonardo M.; Garçon, Daniela P.; Augusto, Alessandra [UNESP]; Faria, Samuel C.; McNamara, John C.; Leone, Francisco A. (Elsevier, 2025)
The whiteleg marine shrimp Penaeus vannamei, originally from the Eastern Pacific Ocean, now inhabits tropical waters across Asia and Central and Southern America. This benthic species exhibits rapid growth, wide salinity and temperature tolerance, and disease resistance. These physiological traits have led to extensive research on its osmoregulatory mechanisms, including next-generation sequencing, transcriptomic analyses, and lipidomic responses. In crustaceans, osmotic and ionic homeostasis is primarily maintained by the membrane-bound metalloenzyme (Na+, K+)-ATPase. However, little is known about how various ligands modulate this enzyme in P. vannamei. Here, we examined the kinetic characteristics of the gill (Na+, K+)-ATPase to get biochemical insights into its modulation. A prominent immunoreactive band of ~120 kDa, corresponding to the (Na+, K+)-ATPase alpha-subunit, was identified. The enzyme exhibited two ATP hydrolyzing sites with K0.5 = 0.0003 ± 0.00002 and 0.05 ± 0.003 mmol L−1 and was stimulated by low sodium ion concentrations. Potassium and ammonium ions also stimulated enzyme activity with similar K0.5 values of 0.08 ± 0.004 and 0.06 ± 0.003 mmol L−1, respectively. Ouabain inhibition profile suggested a single enzyme isoform with a KI value of 2.10 ± 0.16 mmol L−1. Our findings showed significant kinetic differences in the (Na+, K+)-ATPase in Penaeus vannamei compared to marine and freshwater crustaceans. We expect our results to enhance understanding of the modulation of gill (Na+, K+)-ATPase in Penaeus vannamei and to provide a valuable tool for studying the shrimp's biochemical acclimation to varying salinity conditions.
Keywords: (Na+; Ammonium affinity; ATP binding site; K+)-ATPase kinetics; Ouabain binding site; Sodium stimulation